γδ T Cells and Their Potential for Immunotherapy - Wu, Yan-Ling (Ivyspring International Publisher, 2014)
Vγ9Vδ2 (also termed Vγ2Vδ2) T cells, a major human peripheral blood γδ T cell subset, recognize microbial (E)-4-hydroxy-3-methylbut-2-enyl diphosphate and endogenous isopentenyl diphosphate in a TCR-dependent manner. The recognition does not require specific accessory cells, antigen uptake, antigen processing, or MHC class I, class II, or class Ib expression. This subset of T cells plays important roles in mediating innate immunity against a wide variety of infections and displays potent and broad cytotoxic activity against human tumor cells. Because γδT cells express both natural killer receptors such as NKG2D and γδ T cell receptors, they are considered to represent a link between innate and adaptive immunity. In addition, activated γδ T cells express a high level of antigen-presenting cell-related molecules and can present peptide antigens derived from destructed cells to αβ T cells. Utilizing these antimicrobial and anti-tumor properties of γδ T cells, preclinical and clinical trials have been conducted to develop novel immunotherapies for infections and malignancies. Here, we review the immunological properties of γδ T cells including the underlying recognition mechanism of nonpeptitde antigens and summarize the results of γδ T cell-based therapies so far performed. Based on the results of the reported trials, γδ T cells appear to be a promising tool for novel immunotherapies against certain types of diseases.